ANALISIS PENGARUH KARAKTERISTIK PEKERJAAN DAN PEMBERDAYAAN TERHADAP KINERJA PEGAWAI DENGAN MEDIASI KOMITMEN ORGANISASIONAL ( STUDI PADA PDAM TIRTO PANGURIPAN KABUPATEN KENDAL ) - Atty Prihatini, 11.42.02.0065 (Students Journal of Economic and Management, 2013)
The purpose of this study is to examine how big influence of job caracteristic and empowerment towards employeeâs performance in PDAM Tirto Panguripan Kendal. The object populations of this study are permanent employees, sampling methode is using cencus with all the populations as a sample. Primer data of this study using source respondenceâs feedback or questionnaireÂ given to them.Data examination techniques of this study covers instrument test, model test, hypoteses test and mediate test. The result showed ability of models to correctly performed variable relations of job caracteristic, empowerment and organizational commitment are good enoughThe result showed, job characteristic , empowerment and organizational commitmen having positif influence towards PDAM Tirto Panguripan Kendal. Keywords : job characteristic, empowerment, organizational commitment and employeeâs performance